Impact of High Temperature on Oocytes and Embryos: A Review - Wakil, Abubakar Muhammad; Abba, Abdulhamid; Yadav, Prem Singh (Animal Reproduction Update, 2021)
High temperature is one of the leading factors for decline reproductive performance in livestock and other species as a result of heat stress causing severe economic losses. The embryonic death causes due to heat stress is having multifactorial mechanism in live animal. Heat stress could influence reproductive physiology through modulating blood flow to the reproductive tract, ovarian steroid concentrations and patterns of follicular development. It is difficult for embryos to survive in the increase an oviductal and uterine temperature which is coincident with heat stress. In vitro culture of embryos at high temperatures has been reported to affect embryonic development. Similarly, increased in vitro culture temperatures can compromise oocyte activity and reduce fertilization rate. Studies have demonstrated that there were lethal effects of heat shock on in vitro cultured embryos of cattle at 41.0 - 43.0°C. However, these experimental temperatures are higher than those generally experienced by heat-stressed cows which ultimately reduced their fertility. Furthermore, a lot of research have been conducted in livestock species all indicating that exposure to high temperature is detrimental to oocytes and embryonic developmental processes as it leads to cell damage and may interfere with oocyte maturation, and fertilization process. It concludes that the longer exposure of oocytes and embryos to high temperatures causes more damage to oocytes and embryos.
Keywords: Heat stress; Temperature, Fertility; Reproduction; Follicle; Oocytes; Embryos